Injection therapy for base of thumb osteoarthritis: a systematic review and meta-analysis. Issue 9 (11th September 2019) - Riley, Nicholas; Vella-Baldacchino, Martinique; Thurley, Neal; Hopewell, Sally; Carr, Andrew J; Dean, Benjamin John Floyd
Abstract : Objective: To evaluate the effectiveness of injection-based therapy in base of thumb osteoarthritis. Design: Systematic review and meta-analysis. Data sources: MEDLINE and EMBASE via OVID, CINAHL and SPORTDiscus via EBSCO were searched from inception to 22 May 2018. Study selection: Randomised controlled trials (RCTs) and non-RCTs of adults with base of thumb osteoarthritis investigating an injection-based intervention with any comparator/s. Data extraction and analysis: Data were extracted and checked for accuracy and completeness by pairs of reviewers. Primary outcomes were pain and function. Comparative treatment effects were analysed by random-effects model for short-term and medium-term follow-up. Results: In total, 9 RCTs involving 504 patients were identified for inclusion. All compared different injection-based therapies with each other, no studies compared an injection-based therapy with a non-injection-based intervention. Twenty injection-based intervention groups were present within these nine trials, consisting of hyaluronic acid (n=9), corticosteroid (n=7), saline placebo (n=3) and dextrose (n=1). Limited meta-analysis was possible due to the heterogeneity in the injections and outcomes used, as well as incomplete outcome data. Meta-analysis of two RCTs (92 patients) demonstrated reduced Visual Analogue Scale pain on activity with corticosteroid versus hyaluronic acid (mean difference (MD) −1.32, 95% CI −2.23 to −0.41) in the medium term, but no differences in other measures of pain or function in the short term and medium term. Overall, the available evidence does not suggest that any of the commonly used injection therapies are superior to placebo, one another or a non-injection-based comparator. Conclusion: Current evidence is equivocal regarding the use of injection therapy in base of thumb osteoarthritis, both in terms of which injection-based therapy is the most effective and in terms of whether any injection-based therapy is more effective than other non-injection-based interventions. Given limited understanding of both the short-term and long-term effects, there is a need for a large, methodologically robust RCT investigating the commonly used injection therapies and comparing them with other therapeutic options and placebo. PROSPERO registration number: CRD42018095384.